Effects of dispersal barriers and geographic distance on the genetic structure of a narrowly distributed frog in a spatially structured landscape. (31st August 2019) - Pan, T.; Zhou, K.; Zhang, S.‐L.; Shu, Y.‐L.; Zhang, J.‐H.; Li, E.; Wang, M.‐S.; Yan, P.; Wu, H.‐L.
Abstract: Landscape features (e.g., mountains and rivers) can act as barriers to dispersal and gene flow, and therefore impede population connectivity, increasing genetic differentiation between populations. The concave‐eared torrent frog ( Odorrana tormota ) is a rare, stream‐associated species in eastern China. In this study, we investigated the genetic structure and population demography of this narrowly distributed frog based on mitochondrial Cyt b gene and seven nuclear microsatellite loci. As a result, we found that the rare frog still preserved a relatively high level of genetic diversity compared to some other amphibia. Population structure analyses distinctly identified three or four tentative genetic clusters for the species in the study area. Additionally, by fine‐scale spatial autocorrelation analysis, significant positive genetic structure was uncovered in the shortest distance classes (0–5 km, 5–10 km). Demographic analyses revealed a population expansion (0.075–0.017 Mya) and 15 times population decline ( c . 9000 years ago). In conclusion, we supposed that stable montane environments and associated historical population expansion might provide an opportunity for the species to harbor high genetic diversity. The relatively recent population decline might be correlated with climate change as well as genetic differentiation among populations. In addition, our results showed that, on a small landscape scale, dispersal is closely linked to geographic distance and the presence of river systems may not substantially affect the genetic structure for the narrowly distributed O. tormota . Abstract : The concave‐eared torrent frog ( Odorrana tormota ) is a rare, stream‐associated species in eastern China. In this study, we investigated the genetic structure and population demography of this narrowly distributed frog based on mitochondrial Cyt b gene and seven nuclear microsatellite loci. As a result, we found that the rare frog still preserved a relatively high level of genetic diversity compared to some other amphibia. In conclusion, we supposed that stable montane environments and associated historical population expansion might provide an opportunity for the species to harbor high genetic diversity. The relatively recent population decline might be correlated with climate change as well as genetic differentiation among populations.